Singapore : Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This paper outlines that the banking sector remains healthy, backed by high capital, liquidity, provisioning and profitability ratios. Sector-wide nonperforming loans (NPLs) have increased slightly (to 2 percent in 2017:Q1), due largely to stresses in the Oil and Gas (O and G) services sector. Banks have responded by increasing provisions (using forward-looking measures of impairment) and restructuring their loans. Overall, the banking sector is well-positioned to withstand shocks. Capital and liquidity positions are sufficiently strong and well above regulatory requirements. Capital and liquidity positions of the local banking groups remain strong. Liquidity coverage ratios (LCR) of all three major banks remained high and rose in 2016:Q4, remaining well above the regulatory limits. The turnaround in bank's profitability (especially the strong performance in 2017:Q1) is attributed to two factors: an acceleration in credit growth and increases in fee income from wealth management services. Local banks have been a key factor behind the wealth management sector's growth and its main beneficiary.